If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(6p + 2) = 4p + -12 Reorder the terms: -6(2 + 6p) = 4p + -12 (2 * -6 + 6p * -6) = 4p + -12 (-12 + -36p) = 4p + -12 Reorder the terms: -12 + -36p = -12 + 4p Add '12' to each side of the equation. -12 + 12 + -36p = -12 + 12 + 4p Combine like terms: -12 + 12 = 0 0 + -36p = -12 + 12 + 4p -36p = -12 + 12 + 4p Combine like terms: -12 + 12 = 0 -36p = 0 + 4p -36p = 4p Solving -36p = 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. -36p + -4p = 4p + -4p Combine like terms: -36p + -4p = -40p -40p = 4p + -4p Combine like terms: 4p + -4p = 0 -40p = 0 Divide each side by '-40'. p = 0.0 Simplifying p = 0.0
| 7m+1=5m-13 | | 2s-2=25+5s | | 9m-25=-19+7m | | 10y-6=7y+3 | | 9x+7=2x-5 | | 7p+4=-p+9+2+3p | | 1/2x-4=17 | | 8-2y+2y+3=3 | | 4y=2(2+12) | | 5(k+5)=-7 | | 4x^5-x^3-240=0 | | 3.52=2.552-4.25+6.25 | | .2847x+30000000=x | | -8=1(-9t+27) | | 4X+10+175-2x=180 | | -8=1(-9+27) | | 1.2x^2+.4x=.50 | | (64n^12)^-1/6 | | 4x=1/1024 | | 4x=3(x+3)+4 | | 8t-40=12t+30-10 | | 2z-2=-14+6z | | 6t-14=13+9t | | 2(3+4x)-5=25 | | 3x-23=2x-14 | | 3x+4=4(X-3) | | 5/9=10/x | | .25x+20=50 | | 3y^2-y=equation | | 3y^2-y= | | 12x^4-60x^2-432=0 | | 120=10x+10 |